Cohabitation and Social Roles of Homosexual Couples: Ethnography of Lesbian Couples in Tasikmalaya City - Erna Ermawati Chotim; Ramadhini Setia Astuti (Budapest International Research and Critics University, 2021)
This study aims to determine the views of lesbian couples in interpreting the cohabitation they do and the social roles they live. The method used in this research is a qualitative method with a descriptive approach. Data collection was carried out using interview, observation, and documentation techniques. The interview technique was carried out for lesbian couples who performed cohabitation actions at a boarding house in Tasikmalaya. The observations in this study used participant observation techniques carried out for one year. The results showed that cohabitation by a lesbian couple could be seen from three things. First, cohabitation is done as a meaning based on compassion, protection, and responsibility. Second, cohabitation is performed because the boarding environment does not hinder or interfere with their existence. This condition can occur because lesbian couples conduct good social interactions with their surroundings. Third, the actions of cohabitation can cover up their sexual orientation in the name of friendship as fellow women. The social role of lesbian couples is not different from heterosexual couples; men are played by “Butchy”, while women are played by “fame”. In Tasikmalaya, the existence of lesbian couples tends to be closed. They are not free to carry out their social roles. The openness of roles is limited to the environment they live by conducting reference groups.